Impacts of nozzle geometry on spray combustion of high pressure common rail injectors in a constant volume combustion chamber. (1st September 2016) - Yao, Chunde; Geng, Peilin; Yin, Zenghui; Hu, Jiangtao; Chen, Dalu; Ju, Yusheng
Abstract: Diesel engine performance and emissions are closely related to fuel atomization and spray processes, which in turn are strongly influenced by nozzle geometry. In this study, five kinds of single-hole cylindrical injectors which have different orifice diameters (0.13–0.23 mm) and lengths (0.7–1.0 mm) were employed to research the effects of the nozzle geometry on spray droplet size distribution and corresponding combustion characteristics. The spray droplet size spatial distribution was measured with the Phase Doppler Particle Analyzer (PDPA). The results show that the Sauter Mean Diameter (SMD) reduces with the increase of the distance from injector tip and the SMD of the central axis is bigger than that of the periphery. With the increase of the injection pressure (40–120 MPa), the spray SMD decreases significantly. In addition, as the orifice diameter goes smaller, the SMD decreases and the effect of the orifice diameter on the spray SMD becomes weak. Meanwhile, as the orifice length goes longer, the SMD decreases when the orifice diameter is 0.13 mm. And then, the combustion characteristics were experimentally investigated in a constant volume chamber with optical access. Time-resolved images of the natural luminosities (indicator of soot) from the combustion process were captured by high speed camera and combustion pressure was also acquired. It is found that there is a good corresponding relationship between spray SMD, combustion heat release rate and flame luminosity. That is to say, the way to decrease SMD reduces greatly the natural luminosities and improves combustion heat release rate. This article presents the effects of nozzle geometry on droplet size distribution and combustion, and provides important references for injector manufacture.